Humor dalam Tabligh Sisipan yang Sarat Estetika - Ridwan, Aang (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2010)
Joke in tablig constitute sweetener/cosmetics that able to increase attractiveness and effectivity strategy to care attention level of audiences in hearing tablig. Joke in tablig have a lot of functions as: (1) medical function as tool to care healthy and cure physical desease. (2) psychological function born psychological quiet, emotion stability, relaxsation, because of man can meet pleasure andÂ happy andÂ can decrease tension. (3) intellectual and social function increase intellectual and emotional question, and (4) social function as medium social critics.